The Relationship Between Exclusive Breastfeeding And Stunting Incidence In Toddlers Aged 24-60 Months At The Panombean Panei Health Center - Kurnia Purba, Amelia; Halim, Yeni; Meldawati, Meldawati (Syntax Corporation Indonesia, 2024)
Indonesia as a developing country has many health problems, one of these problems is stunting. According to WHO, stunting is a condition where a child's z-score is less than -2 SD/standard deviation as measured on the WHO growth curve. Many factors cause toddlers to experience stunting, such as poor nutritional status during the mother's pregnancy, parenting patterns, and exclusive breastfeeding. Exclusive breastfeeding is the initial food for babies because it contains essential nutrients for immunity so that babies do not get infected easily. In North Sumatra, the stunting incidence rate is 21.1%, especially in Simalungun Regency, the stunting incidence rate is 17.4%. Seeing the conditions that occurred, interest arose in conducting research in the Simalungun Regency area, specifically in the Panombean Panei area. This research uses observational analytical methods with a cross sectional study research design. The sampling technique used in this research was total sampling with a total of 50 toddlers who met the criteria. The assessment of exclusive breastfeeding was carried out by completing a questionnaire by mothers of toddlers. The statistical test used is Chi-Square. The research results showed that 29 (58%) toddlers were given breast milk non-exclusively, so there were 21 (42%) stunted toddlers and 8 (16%) normal toddlers. There are 21 (42%) toddlers who receive exclusive breast milk, of which 9 (18%) toddlers are stunted and 12 (24%) toddlers are normal. The results of the analysis show a p-value = 0.035, which means there is a relationship between exclusive breastfeeding and the incidence of stunting. The conclusion of this research is that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-60 months at the Panombean Panei Health Center.